Exposing the latent phenotype of Gulf War Illness: examination of the mechanistic mediators of cognitive dysfunction - Burzynski, Hannah E.; Reagan, Lawrence P. (Frontiers in Immunology, 2024)
Though it has been over 30 years since the 1990-1991 Gulf War (GW), the pathophysiology of Gulf War Illness (GWI), the complex, progressive illness affecting approximately 30% of GW Veterans, has not been fully characterized. While the symptomology of GWI is broad, many symptoms can be attributed to immune and endocrine dysfunction as these critical responses appear to be dysregulated in many GWI patients. Since such dysregulation emerges in response to immune threats or stressful situations, it is unsurprising that clinical studies suggest that GWI may present with a latent phenotype. This is most often observed in studies that include an exercise challenge during which many GWI patients experience an exacerbation of symptoms.Unfortunately, very few preclinical studies include such physiological stressors when assessing their experimental models of GWI, which creates variable results that hinder the elucidation of the mechanisms mediating GWI. Thus, the purpose of this review is to highlight the clinical and preclinical findings that investigate the inflammatory component of GWI and support the concept that GWI may be characterized as having a latent phenotype. We will mainly focus on studies assessing the progressive cognitive impairments associated with GWI and emphasize the need for physiological stressors in future work to create a more unified hypothesis that can identify potential therapeutics for this patient population.